Pričakovanja vzgojiteljev predšolskih otrok, vezana na njihov profesionalni razvoj - Hmelak, Maja; Lepičnik Vodopivec, Jurka (Revija za elementarno izobraževanje, 2013)
Expectations of Preschool Teachers About Their Professional Development. In this discourse we want to shed some light on preschool teachers’ professional development, focusing on their professional and personal expectations. The first part includes a short presentation of modern trends for an ever-increasing preschool teacher professionalism, which also relates to their own (ever-increasing) expectations. That is followed by an analysis based on our empirical study which we carried out on a population of 616 Slovenian and Croatian preschool education students and preschool teachers. Those analyses revealed a series of interesting (expected/unexpected) similarities and differences in preschool teachers’ expectations about their professional development based on their background (teacher, student), gender (male, female), status (beginners, established, experienced), and country (Slovenia, Croatia).
Keywords: professional development; expectations; preschool teacher; preschooler